Dissolving capacity and volume expansion of carbon dioxide in chain n-alkanes - Haishui HAN; Shiyi YUAN; Shi LI; Xiaolei LIU; Xinglong CHEN (Petroleum Exploration and Development, 2015)
Five kinds of n-alkanes, which have high proportions in crude oil from China, were mixed with CO2 of different molar fractions forming oil-gas systems. The dissolution of CO2 in the five n-alkanes and the system volume swelling were studied through the constant component expansion (CCE) experiments in different temperatures. The pressure-volume curves of the n-alkanes–CO2 systems are not strictly two-part straight lines. The bending degree is affected by the parameters of temperature, pressure, CO2 molar fraction and n-alkanes. Bubble point pressure of the oil-CO2 system is a linear relationship with the temperature. Besides, as the CO2 fraction increases, the bubble point pressure goes up largely. There is a fact that the CO2 solubility in different kinds of alkanes is nearly the same in low pressure condition, while the solubility is inversely proportional to the carbon number in high pressure. The dissolution of CO2 may swell the system, and temperature and pressure are not the main reasons. However, the swelling factor increases quickly as the CO2 molar fraction goes up, and lowers with the carbon number increase. The oil swelling has a great significance for oilfield development and well production. Key words: n-alkanes, carbon dioxide, CCE experiment, solubility, volume swelling